Coaching and barriers to weight loss: an integrative review - Muñoz Obino, Karen Fernanda (Diabetes Metab Syndr Obes, 2016)
INTRODUCTION: Coaching is proposed to raise a patient’s awareness and responsibility for their health behaviour change by transforming the professional–patient relationship. OBJECTIVE: To review the scientific literature on how coaching can assist in weight loss and improve a patient’s state of health. METHODOLOGY: An integrative literature search was performed using PubMed, Latin American and Caribbean Literature in Health Sciences, and Scientific Electronic Library Online. We selected articles that were published in Portuguese, English, and Spanish over the last 10 years. Data analysis was performed using a validated data collection instrument. RESULTS: Among the 289 articles identified in the search, 276 were excluded because they did not address the leading research question, their full texts were not available on the Internet, or they were duplicate publications. Therefore, for the analysis, we selected 13 articles that we classified as randomized clinical studies (46.15%; n=6), cohort studies (30.76%; n=4), cross-sectional studies (7.69%; n=1), case studies (7.69%; n=1), and review articles (7.69%; n=1). Joint intervention (combined in-person and telecoaching sessions) constituted the majority of session types. The use of technical coaching was superior in reducing anthropometric measurements and increasing the levels of motivation and personal satisfaction compared with formal health education alone. CONCLUSION: Coaching is an efficient, cost-effective method for combining formal education and treatment of health in the weight-loss process. Additional randomized studies are needed to demonstrate its effectiveness with respect to chronic disease indicators.